THE OLIVINE--ORTHOPYROXENE--SPINEL OXYGEN GEOBAROMETER, THE NICKEL PRECIPITATION CURVE, AND THE OXYGEN FUGACITY OF THE EARTHS UPPER MANTLE - O'Neill H.St.C.; Wall V.J. (My University, 1987)
The common upper mantle assemblage olivine-orthopyroxene-spinel may be used to calculate the oxygen fugacity at which mantle-derived peridotites have equilibrated. The equilibrium has been calibrated using the large amount of existing data on the thermodynamic properties of each phase in this assemblage. A by-product of this procedure is a new calibration of the olivine-spinel Mg-Fe2+ exchange geothermometer. Application of the equilibrium to a variety of peridotite xenoliths indicates that the oxygen fugacity of the upper mantle lies between the quartz-fayalite-magnetite (QFM) and wüstite-magnetite (WM) oxygen buffers; the few apparent exceptions to this rule may be due to analytical error, particularly in the Fe3+ content of the spinet phase. In fact, the determination of Fe3+ in spinet is at present the limiting factor in the accurate application of the method: within this limitation, the presently available evidence suggests that the oxygen fugacity of the mantle may be laterally homogeneous over wide regions, but may also show small differences between these regions. The fluid species in the system C-H-O at such oxygen fugacities are predominantly CO2 and/or H2O, and not CH4/H2 The minimum possible oxygen fugacity of the mantle is given by the nickel content of olivine in equilibrium with orthopyroxene; for typical mantle compositions this minimum curve is virtually coincident with the iron-wüstite (IW) oxygen buffer.